Advertising regulation in two private television stations: Antena 3 and Telecinco - Matellanes Lazo, Mónica (2013)
Nowadays with different Mass Media and the variety of publicities format, every natural or legal person, public or private can communicate every kind of objects and services to the audience with the intention of promoting direct or indirect the contracting of services and properties, rights or responsibilities. In general the publicity is the communication activity which more economic resources destiny. These days the television is the most powerful mass media because it can communicate with visual and audible signal to the audience easier each other. For that, with the analysis of several format and audience strategies in television we can determine every audience strategy of every channel of television in Spain like Antena 3 and Telecinco.